Iron-based / graphene catalyst and preparation method and application thereof

By using FeF2/FeOX heterojunction in the iron-based/graphene catalyst to combine with graphene, the Fe2B catalyst is formed, which solves the problem of poor reversible hydrogen storage performance of existing catalysts after recombination with light metal borohydride, and achieves good low-temperature dehydrogenation performance and reversible hydrogen storage performance.

CN119524887AActive Publication Date: 2025-02-28XIAN TECH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411595534.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-10
Publication Date
2025-02-28
Estimated Expiration
2044-11-10

AI Technical Summary

Technical Problem

After the existing catalyst is compounded with the light metal borohydride, the modified light metal borohydride produced has poor reversible hydrogen storage performance.

Method used

The FeF2/FeOX heterojunction is used to form a Fe2B catalyst to improve the dehydrogenation performance of light metal borohydrides.

Benefits of technology

It significantly reduces the hydrogen release temperature of LiBH4, increases the hydrogen release rate, and effectively improves its reversible hydrogen storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524887A_ABST
    Figure CN119524887A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid hydrogen storage, and discloses an iron-based / graphene catalyst and a preparation method and application thereof, and the iron-based / graphene catalyst comprises a graphene carrier and a FeF2 / FeOX heterojunction loaded on the graphene carrier. The preparation method comprises the following steps: uniformly mixing FeF3. 3H2O, small molecular alcohol and graphene to obtain a precursor solution; the precursor solution is subjected to a hydrothermal reaction at 190-240 DEG C for 20-36 h, and the iron-based / graphene catalyst is obtained. The iron-based / graphene catalyst provided by the invention is a graphene-loaded FeF2 / FeOX heterojunction, has a rich interface, and can provide relatively high catalytic activity. According to the prepared composite hydrogen storage material, various uniform and stable catalysts including FeB, Fe2B and Li3BO3 are formed in situ in the first hydrogen desorption process, all the catalysts have a synergistic effect, the hydrogen desorption temperature of LiBH4 is reduced, the hydrogen desorption speed is increased, and good low-temperature dehydrogenation performance is shown; meanwhile, the reversible hydrogen storage performance of LiBH4 is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state hydrogen storage, and in particular relates to an iron-based / graphene catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen is regarded as the ultimate energy source for mankind due to its zero pollution, abundant storage and low cost. The preparation, storage, transportation and use of hydrogen are the three key technologies for realizing large-scale practical application of hydrogen energy. However, how to store hydrogen in a high capacity, large scale and economical way is a huge technical challenge facing the application of hydrogen energy. LiBH4 has high mass (18.5wt%) and volume (121kg / m 3 ) hydrogen storage density has attracted much attention, but due to Li + and [BH4] - The strong ionic bond between B and H and the strong covalent bond between B and H result in a dehydrogenation temperature usually above 400°C and a slow rate of hydrogen release. In addition, the low reactivity of B to H leads to the growth and agglomeration of particles and phase separation, which requires harsh temperatures (600°C) and hydrogen pressures (35Mpa) for the regeneration of LiBH4, resulting in poor reversible cycle performance.

[0003] The introduction of catalysts can effectively reduce the dehydrogenation temperature of LiBH4 and increase its hydrogen release rate. Existing catalysts include transition metals such as Ni, Fe, Co and Mg; metal fluorides such as VCl3, CeCl3 and TiCl3; metal oxides such as Fe2O3, V2O5, Nb2O5, TiO2 and SiO2; metal fluorides such as FeF3, TiF3, CeF3, NbF5 and AlF3 have been widely reported. For example: Yuan et al., Journal of Alloys and Compounds 2013, 557: 124-129. The 3LiBH4+AlF3 composite system prepared by ball milling absorbs hydrogen for 24 hours at 450°C and 9.2MPa, and then is heated to 600°C for the second dehydrogenation, and 1wt% H2 is released. However, after these catalysts are compounded with light metal borohydrides, the reversible hydrogen storage performance of the modified light metal borohydrides obtained is poor. Therefore, there is an urgent need to develop a catalyst that can improve the reversible hydrogen storage performance of modified light metal borohydrides. Summary of the invention

[0004] The present invention provides an iron-based / graphene catalyst and a preparation method and application thereof, which solves the problem that after the catalyst prepared in the prior art is compounded with a light metal borohydride, the reversible hydrogen storage performance of the prepared modified light metal borohydride is poor.

[0005] The first aspect of the present invention provides an iron-based / graphene catalyst, comprising a graphene carrier, and FeF2 / FeO2 supported on the graphene carrier. X Heterojunction.

[0006] The second object of the present invention is to provide a method for preparing the iron-based / graphene catalyst, which specifically comprises the following steps:

[0007] Evenly mixing FeF3·3H2O, small molecule alcohol and graphene to obtain a precursor solution;

[0008] The precursor solution is hydrothermally reacted at 190-240° C. for 20-36 hours to obtain the iron-based / graphene catalyst.

[0009] The morphology of the iron-based catalyst is affected by the hydrothermal reaction time. In the first 0-5 hours, an aggregate of nanoparticles is formed. As the reaction time is further extended to 5-15 hours, the nanoparticles begin to assemble and gradually produce smooth nanosheets. Further increasing the reaction time to more than 20 hours, a rod-shaped iron-based catalyst is obtained.

[0010] Preferably, the small molecule alcohol is one of n-propanol, methanol, ethanol, isopropanol and n-butanol.

[0011] Preferably, when the small molecule alcohol is n-propanol, the ratio of FeF3·3H2O, n-propanol and graphene is 10 mg:6 mL:5 mg.

[0012] The third object of the present invention is to protect the use of the iron-based / graphene catalyst in catalyzing the preparation of light metal borohydrides.

[0013] A method for preparing a composite hydrogen storage material, comprising:

[0014] Under an inert atmosphere, the iron-based / graphene catalyst and the light metal borohydride are ball-milled for 2-3 hours to obtain the composite hydrogen storage material; wherein the mass ratio of the iron-based / graphene catalyst to the light metal borohydride is 6-8:2-4.

[0015] Preferably, the mass ratio of the iron-based / graphene catalyst to the light metal borohydride is 3:7.

[0016] Preferably, the light metal borohydride is one of LiBH4, NaBH4, and Mg(BH4)2.

[0017] Preferably, the ball milling speed is 400-500 rpm, and the ball milling time is 2-3 h.

[0018] The fourth object of the present invention is to protect the composite hydrogen storage material obtained by the preparation method.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) The iron-based / graphene catalyst provided by the present invention is graphene-supported FeF2 / FeO X Heterojunction, due to FeF2 / FeO X The heterojunction has rich interfaces and provides multiple active sites, which can provide high catalytic activity. During ball milling, it reacts with LiBH4 as follows: LiBH4+FeF2 / FeO X →Li m Fe n O p +Fe2B+LiF+B2O3+H2↑, Fe2B catalyst is generated on the surface of LiBH4. At the same time, since light metal borohydride is a strong reducing agent, and the iron agent / graphene catalyst has high oxidizing property, it undergoes redox reaction with light metal borohydride during ball milling. It is detected that Fe2B is formed on the surface of borohydride during ball milling, which can effectively catalyze the dehydrogenation of light metal borohydride. The preparation process of the composite hydrogen storage material of the present invention is simple, the cycle is short, the requirements for instruments and equipment are not high, and it is easy to implement.

[0021] 2) The composite hydrogen storage material provided by the present invention forms multiple uniform and stable catalysts in situ during the first dehydrogenation: FeB, Fe2B and Li3BO3. Taking light metal borohydride LiBH4 as an example, since LiBH4 and iron agent / graphene catalyst undergo chemical reactions during the heating process, multiple catalysts are introduced, and all catalysts work synergistically to reduce the dehydrogenation temperature of LiBH4, accelerate the dehydrogenation rate, and show good low-temperature dehydrogenation performance; more importantly, the reversible hydrogen storage performance of LiBH4 is effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 FeF2 / FeO prepared in Example 1 X @G’s XRD;

[0023] Figure 2 FeF2 / FeO prepared in Example 1 X @G’s Raman spectrum;

[0024] Figure 3 FeF2 / FeO prepared in Example 1 X @G's Fe 2p: a, F 1s: b, O 1s: c; C 1s: d XPS spectra;

[0025] Figure 4 FeF2 / FeO prepared in Example 1 X@G's SEM (100nm): a, SEM (250nm): b, TEM (5nm): c, TEM (100nm): d and EDS image: e;

[0026] Figure 5 The mLiBH4-n (FeF2 / FeO X @G) XRD spectrum;

[0027] Figure 6 The mLiBH4-n (FeF2 / FeO X @G) FTIR spectrum;

[0028] Figure 7 The mLiBH4-n (FeF2 / FeO X @G) Fe 2p, F 1s, O 1s and C 1s XPS spectra;

[0029] Figure 8 The mLiBH4-n (FeF2 / FeO X @G) non-isothermal hydrogen release curve;

[0030] Fig. 9 The mLiBH4-n (FeF2 / FeO X @G) HRTEM image;

[0031] Fig.10 The mLiBH4-n (FeF2 / FeO X @G) Isothermal hydrogen release curve at 350°C;

[0032] Fig.11 The mLiBH4-n (FeF2 / FeO X @G) Isothermal hydrogen release curve at 400°C;

[0033] Fig.12 7LiBH4-3(FeF2 / FeO X @G) Isothermal hydrogen release curves of different cycles;

[0034] Fig.13 7LiBH4-3(FeF2 / FeO X @G) and pristine LiBH4 cyclic hydrogen desorption capacity comparison;

[0035] Fig.14 7LiBH4-3(FeF2 / FeO X@G) XRD patterns of products from different hydrogen absorption and desorption cycles;

[0036] Fig.15 7LiBH4-3(FeF2 / FeO X @G) Fe 2p and B1s XPS spectra of different hydrogen absorption and desorption cycle products;

[0037] Fig.16 7LiBH4-3(FeF2 / FeO X @G) HRTEM image;

[0038] Fig.17 This is the SEM image of the original LiBH4 after 5 cycles;

[0039] Fig.18 7LiBH4-3(FeF2 / FeO X @G) SEM image after 10 cycles. DETAILED DESCRIPTION

[0040] The technical solutions in the present invention will be described clearly and completely below in conjunction with the specific implementation of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The methods described in the embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0042] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. Among them, A and B can be singular or plural; the single symbol " / " means "or".

[0043] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of A, B or C", or "at least one of A, B and C" can represent any one of A, B, C, or A+B, or A+C, or B+C, or A+B+C, where A, B, C can be single or multiple, respectively.

[0044] In the following description of this embodiment, the order of serial numbers does not mean the order of execution. Some or all of the steps can be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of this embodiment.

[0045] In the following description of the present embodiment, the numerical range should be understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Any stated value or intermediate value in the stated range and any other stated value or each smaller range between the intermediate values ​​in the stated range are also included in the present embodiment, and the upper and lower limits of the smaller range can be independently included or excluded in the range.

[0046] Unless otherwise stated, the technical / scientific terms used in the present embodiment have the same meanings as those generally understood by those skilled in the art to which the present application belongs. Although the present application only describes preferred methods and materials, any similar or equivalent methods and materials may also be used in the implementation or testing of the present application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of any conflict with any incorporated document, the content of this specification shall prevail.

[0047] Example 1

[0048] A method for preparing an iron-based / graphene catalyst, the specific experimental operation steps are as follows:

[0049] Step 1: Weigh 100 mg FeF3·3H2O and 60 mL n-propanol, pour them into a 100 mL polytetrafluoroethylene liner, and stir at room temperature at 100 rpm for 30 min. Then weigh 50 mg graphene and add it to the above solution, continue stirring for 1 hour, and obtain a precursor solution.

[0050] Step 2: The precursor solution is loaded into a hydrothermal reaction kettle, and then transferred to a forced air drying oven, and a hydrothermal reaction is carried out at 210° C. for 24 hours to obtain a reaction product.

[0051] Step 3: Wash the reaction product three times with ethanol and centrifuge it at 7000 rpm for 3 min. Separate the solid and dry it in a vacuum oven at 100°C for 8 h to obtain the iron-based / graphene catalyst. The prepared iron-based / graphene catalyst is an in-situ generated multiphase stable catalyst, denoted as FeF2 / FeO X @G.

[0052] Figure 1 FeF2 / FeO XIn the FeF2 XRD spectrum in @G, only the FeF2 phase with the space group of P42 / mnm (PDF#45-1026) was detected, indicating that the FeF2 synthesis was successful and no other phases were detected. In addition, due to the amorphous structure of graphene, no diffraction peaks of graphene were observed in the XRD pattern.

[0053] Figure 2 FeF2 / FeO X @G Raman graph of sample FeF2 / FeO X Raman spectrum of @G( Figure 2 ) at 1340 and 1580cm -1 There are two peaks at , which are attributed to the disorder-induced carbon (d band) and graphite structure (g peak) in the graphene matrix, respectively.

[0054] Figure 3 FeF2 / FeO X The XPS spectrum of @G, combined with the XRD spectrum, confirms the existence of FeF2 and some amorphous FeO X .FeF2 / FeO X @G's C1s( Figure 3 a) Deconvolution into 5 peaks at 284.0, 285.1, 286, 287.9 ​​and 290.1 ​​eV, corresponding to the binding energy of C=C, CC, C=O, O=CO and π-π bond, respectively. There is a peak at 284.0 eV, indicating the presence of graphene, and most of the carbon atoms are in the SP2 orbital hybridization region. High-resolution F1s ( Figure 3 b) shows a typical symmetrical peak at 684.6 eV, which is assigned to Fe 2+ -F bond. FeF2 / FeO x @G's O1s zone ( Figure 3 c), four main peaks were observed at 529.7, 531.2, 533.0 and 535.0 eV, belonging to Fe-O, CO, C=O and FO bonds, respectively. Figure 3 As shown in d, the Fe 2p nuclear energy level spectrum shows obvious satellite peaks at 714.6 and 719.1 eV, which belong to Fe 2+ and Fe 3+ , indicating that FeF2 / FeO X @Fe exists in G 2+ and Fe 3+ Combining O1s and F1s spectral analysis, it was confirmed that FeF2 / FeO X FeO exists in @G X The above XRD, Raman and XPS results show that FeF2 / FeO x @G is composed of FeF2, amorphous FeOx and graphene.

[0055] Figure 4 FeF2 / FeO X @G sample morphology, EDS spectrum further confirmed the prepared FeF2 / FeO X @G The sample contains amorphous FeO X . Figure 4 a is FeF2 / FeO X @G SEM morphology shows that some rod-like structures grow on the graphene matrix, and these rod-like structures are entangled with each other. In addition, XRD and XPS analysis confirmed that these rods are FeF2 and amorphous FeO X TEM observation ( Figure 4 b) Display FeF2 / FeO X @G has a distinct rod-like morphology, with a large number of gray-black rod-like particles dispersed in a light gray matrix. These gray-black rods are FeF2 and amorphous FeO X , while the light grey layer is the graphene matrix. HRTEM image ( Figure 4 c) shows the FeF2(111) lattice fringes, with a lattice spacing of 0.234 nm, which is similar to that of amorphous FeO X The close contact between FeF2 and FeO X Dispersed on the graphene surface. In addition, the distribution of O element is similar to that of F and Fe elements ( Figure 4 e), combined with XPS analysis of F1s and Fe 2p, further proves that FeF2 / FeO X @G sample contains FeF2 and amorphous FeOx, which are evenly dispersed on the graphene matrix. Through the above characterization and analysis, graphene-supported rod-shaped FeF2 and amorphous FeOx were successfully synthesized. X .

[0056] The FeF2 / FeO prepared in Example 1 X @G is used to prepare mLiBH4-n (FeF2 / FeO X @G) Composite hydrogen storage system, where m:n = 6:4, 7:3, 8:2.

[0057] Example 2

[0058] A composite hydrogen storage material, the specific preparation process includes the following steps:

[0059] Step 1: Weigh 1.2g LiBH4 and 0.8g FeF2 / FeO in the glove box X @G were loaded into a 220 mL stainless steel ball mill jar in sequence, and then stainless steel ball mill beads with a diameter of 6 mm were added, with a ball-to-material ratio of 100:1.

[0060] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0061] Step 3: Take out the sample from the ball mill and get 6LiBH4-4(FeF2 / FeO X @G) composite system hydrogen storage material.

[0062] Example 3-4: The preparation method of the composite hydrogen storage material is the same as that of Example 2, except that LiBH4 and FeF2 / FeO X @G The added mass ratio is different.

[0063] Example 3

[0064] A composite hydrogen storage material, the specific preparation process includes the following steps:

[0065] Step 1: Weigh 0.7g LiBH4 and 0.3g FeF2 / FeO in the glove box X @G were loaded into a 220 mL stainless steel ball mill jar in sequence, and then stainless steel ball mill beads with a diameter of 6 mm were added, with a ball-to-material ratio of 100:1.

[0066] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0067] Step 3: Take out the sample from the ball mill and get 7LiBH4-3(FeF2 / FeO X @G) composite system hydrogen storage material.

[0068] Example 4

[0069] A composite hydrogen storage material, the specific preparation process includes the following steps:

[0070] Step 1: Weigh 1.2g LiBH4 and 0.8g FeF2 / FeO in the glove box X @G were loaded into a 220 mL stainless steel ball mill jar in sequence, and then stainless steel ball mill beads with a diameter of 6 mm were added, with a ball-to-material ratio of 100:1.

[0071] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0072] Step 3: Take out the sample from the ball mill and get 6LiBH4-4(FeF2 / FeO X @G) composite system hydrogen storage material.

[0073] The amounts of raw materials added in Examples 3 and 4 are shown in Table 1:

[0074] Table 1 Raw material addition amount and ball milling conditions of Examples 3 and 4

[0075]

[0076] The composite samples prepared above were characterized: Figure 5 mLiBH4-n(FeF2 / FeO X @G) XRD spectrum of the composite sample, from which no diffraction peak of FeF2 was found. Figure 6 mLiBH4-n(FeF2 / FeO X The FTIR spectrum of @G) confirmed the presence of LiBH4 in the composite sample. Figure 7 mLiBH4-n(FeF2 / FeO X @G) XPS spectrum, analysis shows that FeF2 / FeO X FeF2 and FeO in @G samples X It reacted with LiBH4 during ball milling and generated a uniformly distributed catalyst Fe2B on the surface of LiBH4. Figure 8 The mLiBH4-n (FeF2 / FeO X @G) non-isothermal hydrogen release curve. Fig. 9 mLiBH4-n(FeF2 / FeO X @G) further illustrates the formation of Fe2B catalyst.

[0077] Comparative Example 1

[0078] A method for preparing a 7LiBH4-3FeF3 composite material, comprising:

[0079] Step 1: In the glove box, weigh 0.7g LiBH4 and 0.3g FeF3 and put them into a 220mL stainless steel ball mill jar in turn, and then put in stainless steel ball mill beads with a diameter of 6mm, with a ball-to-material ratio of 100:1.

[0080] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0081] Step 3: Take out the sample from the ball mill to obtain the 7LiBH4-3FeF3 composite system hydrogen storage material.

[0082] The isothermal dehydrogenation performance test of the prepared 7LiBH4-3FeF3 sample was carried out. The specific steps are as follows:

[0083] Step 1: The test instrument is a Sieverts-type gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0084] Step 2: First, evacuate the chamber, then set up an isothermal test program, heating from room temperature to the target temperature of 400°C at a rate of 10°C / min and keeping the temperature for 150 minutes.

[0085] Step 3: After vacuuming, let it stand for 10 minutes, then click the program and record the data. When the test is completed, close the data recording program and save the test data.

[0086] The prepared composite system was further tested for its cyclic stability. The specific experimental steps are as follows:

[0087] Step 1: The test instrument is a Sieverts gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0088] Step 2: First, the sample is isothermally dehydrogenated, heated from room temperature to the target temperature and kept warm for a period of time until the sample completely releases hydrogen (heated to 400°C at 10°C / min and kept warm for 150 minutes). The dehydrogenated product then absorbs hydrogen, heated to the target temperature under 10MpaH2 pressure and kept warm for a period of time (heated to 450°C at 10°C / min and kept warm for 150 minutes).

[0089] Step 3: Before testing, evacuate the sample and set the test procedure. One isothermal dehydrogenation and one isothermal absorption of hydrogen are considered as one cycle of absorption and dehydrogenation. The cyclic absorption and dehydrogenation capacity is calculated using the dehydrogenation capacity of the sample.

[0090] Comparative Example 27 LiBH4-3FeF2 composite material

[0091] A method for preparing a 7LiBH4-3FeF2 composite material, comprising:

[0092] Step 1: In the glove box, weigh 0.7g LiBH4 and 0.3g FeF2 and put them into a 220mL stainless steel ball mill jar in turn, and then put in stainless steel ball mill beads with a diameter of 6mm, with a ball-to-material ratio of 100:1.

[0093] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0094] Step 3: Take out the sample from the ball mill to obtain the 7LiBH4-3FeF3 composite system hydrogen storage material.

[0095] The isothermal dehydrogenation performance test of the prepared 7LiBH4-3FeF3 sample was carried out. The specific steps are as follows:

[0096] Step 1: The test instrument is a Sieverts-type gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0097] Step 2: First, evacuate the chamber, then set up an isothermal test program, heating from room temperature to the target temperature of 400°C at a rate of 10°C / min and keeping the temperature for 150 minutes.

[0098] Step 3: After vacuuming, let it stand for 10 minutes, then click the program and record the data. When the test is completed, close the data recording program and save the test data.

[0099] The prepared composite system was further tested for its cyclic stability. The specific experimental steps are as follows:

[0100] Step 1: The test instrument is a Sieverts gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0101] Step 2: First, the sample is isothermally dehydrogenated, heated from room temperature to the target temperature and kept warm for a period of time until the sample completely releases hydrogen (heated to 400°C at 10°C / min and kept warm for 150 minutes). The dehydrogenated product then absorbs hydrogen, heated to the target temperature under 10MpaH2 pressure and kept warm for a period of time (heated to 450°C at 10°C / min and kept warm for 150 minutes).

[0102] Step 3: Before testing, evacuate the sample and set the test procedure. One isothermal dehydrogenation and one isothermal absorption of hydrogen are considered as one cycle of absorption and dehydrogenation. The cyclic absorption and dehydrogenation capacity is calculated using the dehydrogenation capacity of the sample.

[0103] Comparative Example 37 LiBH4-3Fe2O3 composite material

[0104] A method for preparing a 7LiBH4-3Fe2O3 composite material comprises:

[0105] Step 1: In the glove box, weigh 0.7g LiBH4 and 0.3g Fe2O3 and put them into a 220mL stainless steel ball mill jar in turn, and then put in stainless steel ball mill beads with a diameter of 6mm, with a ball-to-material ratio of 100:1.

[0106] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0107] Step 3: Take out the sample from the ball mill to obtain the 7LiBH4-3FeF3 composite system hydrogen storage material.

[0108] The isothermal dehydrogenation performance test of the prepared 7LiBH4-3FeF3 sample was carried out. The specific steps are as follows:

[0109] Step 1: The test instrument is a Sieverts-type gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0110] Step 2: First, evacuate the chamber, then set up an isothermal test program, heating from room temperature to the target temperature of 400°C at a rate of 10°C / min and keeping the temperature for 150 minutes.

[0111] Step 3: After vacuuming, let it stand for 10 minutes, then click the program and record the data. When the test is completed, close the data recording program and save the test data.

[0112] The prepared composite system was further tested for its cyclic stability. The specific experimental steps are as follows:

[0113] Step 1: The test instrument is a Sieverts gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0114] Step 2: First, the sample is isothermally dehydrogenated, heated from room temperature to the target temperature and kept warm for a period of time until the sample completely releases hydrogen (heated to 400°C at 10°C / min and kept warm for 150 minutes). The dehydrogenated product then absorbs hydrogen, heated to the target temperature under 10MpaH2 pressure and kept warm for a period of time (heated to 450°C at 10°C / min and kept warm for 150 minutes).

[0115] Step 3: Before testing, evacuate the sample and set the test procedure. One isothermal dehydrogenation and one isothermal absorption of hydrogen are considered as one cycle of absorption and dehydrogenation. The cyclic absorption and dehydrogenation capacity is calculated using the dehydrogenation capacity of the sample.

[0116] Comparative Example 47 LiBH4-3FeO composite material

[0117] A method for preparing a 7LiBH4-3FeO composite material, comprising:

[0118] Step 1: In the glove box, weigh 0.7 g LiBH4 and 0.3 g FeO and put them into a 220 mL stainless steel ball mill jar in turn, and then put in stainless steel ball mill beads with a diameter of 6 mm, with a ball-to-material ratio of 100:1.

[0119] Step 2: Fill the ball mill with 5Mpa Ar as protective gas. Then install the ball mill on the ball mill, set the two-way mode, the speed is 400rpm, the forward and reverse rotation is 30min each, the time interval is 6min, and the operation number is 2 times.

[0120] Step 3: Take out the sample from the ball mill to obtain the 7LiBH4-3FeF3 composite system hydrogen storage material.

[0121] The isothermal dehydrogenation performance test of the prepared 7LiBH4-3FeF3 sample was carried out. The specific steps are as follows:

[0122] Step 1: The test instrument is a Sieverts-type gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0123] Step 2: First, evacuate the chamber, then set up an isothermal test program, heating from room temperature to the target temperature of 400°C at a rate of 10°C / min and keeping the temperature for 150 minutes.

[0124] Step 3: After vacuuming, let it stand for 10 minutes, then click the program and record the data. When the test is completed, close the data recording program and save the test data.

[0125] The prepared composite system was further tested for its cyclic stability. The specific experimental steps are as follows:

[0126] Step 1: The test instrument is a Sieverts gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0127] Step 2: First, the sample is isothermally dehydrogenated, heated from room temperature to the target temperature and kept warm for a period of time until the sample completely releases hydrogen (heated to 400°C at 10°C / min and kept warm for 150 minutes). The dehydrogenated product then absorbs hydrogen, heated to the target temperature under 10MpaH2 pressure and kept warm for a period of time (heated to 450°C at 10°C / min and kept warm for 150 minutes).

[0128] Step 3: Before testing, evacuate the sample and set the test procedure. One isothermal dehydrogenation and one isothermal absorption of hydrogen are considered as one cycle of absorption and dehydrogenation. The cyclic absorption and dehydrogenation capacity is calculated using the dehydrogenation capacity of the sample.

[0129] Table 2 Dehydrogenation performance and cycle performance of different comparative examples

[0130] Group Material system Isothermal dehydrogenation Reversible cycle 2 times Comparative Example 1 <![CDATA[7LiBH4-3FeF3]]> 6.7wt% 4.5wt% Comparative Example 2 <![CDATA[7LiBH4-3FeF2]]> 6.0wt% 4.1wt% Comparative Example 3 <![CDATA[7LiBH4-3Fe2O3]]> 8.7wt% 3.9wt% Comparative Example 4 <![CDATA[7LiBH4-3FeO]]> 6.4wt% 3.6wt%

[0131] The prepared mLiBH4-n(FeF2 / FeO X @G) The composite system is tested for non-isothermal dehydrogenation performance, and the specific steps are as follows:

[0132] Step 1: The test instrument is a Sieverts-type gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0133] Step 2: First, evacuate the chamber, then set up a non-isothermal test program, heating from room temperature to 600°C at 2°C / min.

[0134] Step 3: After vacuuming, let it stand for 10 minutes, then click the program and record the data. When the test is completed, close the data recording program and save the test data.

[0135] See also Fig.10 It can be seen that the initial hydrogen release temperatures of Examples 2-4 are all lower than 100°C, while the dehydrogenation temperature of the original LiBH4 is 310°C. The composite hydrogen storage material prepared by the present invention is more than 200°C lower than the dehydrogenation temperature of the original LiBH4, showing good low-temperature dehydrogenation performance.

[0136] The prepared mLiBH4-n(FeF2 / FeO X @G) The composite system was tested for isothermal dehydrogenation performance, and the specific steps are as follows:

[0137] Step 1: The test instrument is a Sieverts-type gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0138] Step 2: First, evacuate the chamber, then set up an isothermal test program, heating from room temperature to the target temperatures of 350°C and 400°C at 10°C / min and keeping the temperature for 200 minutes.

[0139] Step 3: After vacuuming, let it stand for 10 minutes, then click the program and record the data. When the test is completed, close the data recording program and save the test data.

[0140] See also Fig.11From the isothermal dehydrogenation results at 350℃, mLiBH4-n(FeF2 / FeO X @G) Compared with the original LiBH4, the release rate of hydrogen is significantly accelerated. X @G) When heated at 350℃ for 60min (including 35min heating time), the hydrogen release is almost complete, reaching 6.4wt%, while under the same conditions, the hydrogen desorption rate of the original LiBH4 is only 1.1wt%. 8LiBH4-2(FeF2 / FeO X @G) and 7LiBH4-3(FeF2 / FeO X @G) were kept at 350℃ for 80min (including 35min heating time), releasing 3.6wt% H2 and 7.0wt% H2 respectively. X @G) isothermal dehydrogenation at 400℃, 6LiBH4-4(FeF2 / FeO X @G) and 7LiBH4-3(FeF2 / FeO X @G) completed dehydrogenation within 45 min (including 40 min heating time), and the hydrogen release rates were very similar, reaching 7.6 wt% and 9.3 wt% H2, respectively. X The dehydrogenation kinetics of @G) has been significantly improved, see Fig.11 .

[0141] The system of Example 3 has good dehydrogenation performance and is the best example.

[0142] The composite system prepared in Example 3 was selected to further test its cyclic stability. The specific experimental steps are as follows:

[0143] Step 1: The test instrument is a Sieverts gas-solid reaction device made by Zhejiang University. Approximately 60 mg of sample is loaded for each test, and then the reactor is connected to the hydrogen storage tester.

[0144] Step 2: First, the sample is isothermally dehydrogenated, heated from room temperature to the target temperature and kept warm for a period of time until the sample completely releases hydrogen (heated to 400°C at 10°C / min and kept warm for 150 minutes). The dehydrogenated product then absorbs hydrogen, heated to the target temperature under 10MpaH2 pressure and kept warm for a period of time (heated to 450°C at 10°C / min and kept warm for 150 minutes).

[0145] Step 3: Before testing, evacuate the sample and set the test procedure. One isothermal dehydrogenation and one isothermal absorption of hydrogen are considered as one cycle of absorption and dehydrogenation. The cyclic absorption and dehydrogenation capacity is calculated using the dehydrogenation capacity of the sample.

[0146] See also Fig.12 and Fig.13 Compared with the original LiBH4, 7LiBH4-3(FeF2 / FeO X @G) showed excellent reversible hydrogen storage performance. 7LiBH4-3(FeF2 / FeO X @G) decreased from 9.4wt% in the first cycle to 5.5wt% in the 10th cycle, corresponding to a reversible capacity retention of 58.8wt%. For the original LiBH4, only 4.4wt% H2 was obtained in the first dehydrogenation, and the dehydrogenation capacity dropped to 2.9wt% after 5 cycles.

[0147] In addition, for 7LiBH4-3(FeF2 / FeO X @G) The phase evolution during the composite cycle was analyzed, such as Fig.14 The decomposition and regeneration of LiBH4 under different hydrogen absorption and desorption states can be seen from the XRD spectrum. In addition, the diffraction peaks of Li3BO3 and FeB of the catalyst were observed to exist stably during hydrogen absorption and desorption. Fig.15 7LiBH4-3(FeF2 / FeO X @G) Fe 2p and B1s XPS spectra of different hydrogen absorption and desorption cycle products. The Fe 2p and B1s spectra further confirmed the existence of FeB and Fe2B catalysts and their stable existence in hydrogen absorption and desorption. Combined with XRD analysis, it was proved that a multiphase catalyst was formed in the first dehydrogenation product and the synergy between the catalysts was beneficial to improve the reversible cycle performance of LiBH4. In addition, Fig.16 7LiBH4-3(FeF2 / FeO X @G) HRTEM, where clear lattice fringes can be seen, further confirming the existence of these catalysts.

[0148] Fig.17 This is the SEM image of the original LiBH4 after 5 cycles. Fig.18 7LiBH4-3(FeF2 / FeO X @G) SEM morphology of 10 cycles. It can be seen that the original LiBH4 has serious agglomeration and particle growth after 5 dehydrogenation cycles, and formed large and dense agglomerates. X @G) After 10 dehydrogenation cycles, the product is composed of many small particles, mainly because the graphene in the sample plays a role in dispersing and inhibiting particle growth, preventing product agglomeration, and also making the formed catalyst evenly dispersed.

[0149] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0150] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. An iron-based / graphene catalyst, characterized in that: Comprising a graphene carrier, and FeF2 / FeO loaded on the graphene carrier X Heterojunction.

2. A method for preparing the iron-based / graphene catalyst according to claim 1, characterized in that: The specific steps include: Evenly mixing FeF3·3H2O, small molecule alcohol and graphene to obtain a precursor solution; The precursor solution is hydrothermally reacted at 190-240° C. for 20-36 hours to obtain the iron-based / graphene catalyst.

3. The preparation method according to claim 2, characterized in that: The small molecule alcohol is one of n-propanol, methanol, ethanol, isopropanol and n-butanol.

4. The preparation method according to claim 2, characterized in that: When the small molecule alcohol is n-propanol, the ratio of FeF3·3H2O, n-propanol and graphene is 10 mg:6 mL:5 mg.

5. Use of the iron-based / graphene catalyst according to claim 1 in catalyzing the preparation of light metal borohydrides.

6. A method for preparing a composite hydrogen storage material, characterized in that: include: Under an inert atmosphere, the iron-based / graphene catalyst and the light metal borohydride according to claim 1 are ball-milled for 2-3 hours to obtain the composite hydrogen storage material; wherein the mass ratio of the iron-based / graphene catalyst to the light metal borohydride is 6-8:2-4.

7. The preparation method according to claim 6, characterized in that: The mass ratio of the iron-based / graphene catalyst to the light metal borohydride is 3:

7.

8. The preparation method according to claim 6, characterized in that: The light metal borohydride is one of LiBH4, NaBH4, and Mg(BH4)2.

9. The preparation method according to claim 6, characterized in that: The ball milling speed is 400-500 rpm, and the ball milling time is 2-3 h.

10. A composite hydrogen storage material obtained by the preparation method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Composition for hydrogen generation

    CA2631097A1

  • Defect-rich Fe2O3-FeF2 nano porous film, preparation method and application thereof

    CN107803212A

  • Preparation method of yttrium-nickel hydrogen storage alloy

    CN112921363A

  • Preparation method of graphene-loaded nanosheet transition metal hydride and hydrogen storage material

    CN113148956A

  • Fluorine-doped mesoporous carbon confinement Fe-series catalyst as well as preparation method and application thereof

    CN116550346A